2003
DOI: 10.1152/ajpheart.00251.2002
|View full text |Cite
|
Sign up to set email alerts
|

A1 adenosine receptor overexpression attenuates ischemia-reperfusion-induced apoptosis and caspase 3 activity

Abstract: We tested the hypothesis that myocardial ischemia-reperfusion (I/R)-induced apoptosis is attenuated in transgenic mice overexpressing cardiac A(1) adenosine receptors. Isolated hearts from transgenic (TG, n = 19) and wild-type (WT, n = 22) mice underwent 30 min of ischemia and 2 h of reperfusion, with evaluation of apoptosis, caspase 3 activity, function, and necrosis. I/R-induced apoptosis was attenuated in TG hearts. TG hearts had less I/R-induced apoptotic nuclei (0.88 +/- 0.10% vs. 4.22 +/- 0.24% terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 26 publications
(36 reference statements)
2
42
0
Order By: Relevance
“…Collectively, these studies support a role for gene transcription and/or protein synthesis in the acute effects of adenosine receptor activation. This form of control agrees with adenosine-mediated inhibition of transcriptionally regulated apoptosis postischemia (237,310), possibly via modulating transcription and expression of Bcl-2 and Bax (310).…”
Section: Are Acute Effects Of Adenosine Receptor Activation Entirely supporting
confidence: 68%
See 1 more Smart Citation
“…Collectively, these studies support a role for gene transcription and/or protein synthesis in the acute effects of adenosine receptor activation. This form of control agrees with adenosine-mediated inhibition of transcriptionally regulated apoptosis postischemia (237,310), possibly via modulating transcription and expression of Bcl-2 and Bax (310).…”
Section: Are Acute Effects Of Adenosine Receptor Activation Entirely supporting
confidence: 68%
“…Adenosinergic protection has been clearly established as a mechanism for reducing both oncosis (9, 207, 224, 228, 277, 314) and apoptosis (237,310), leading to substantial reductions in infarct size and injury. Whether adenosinergic responses protect against reversible injury is more difficult to ascertain because both forms of injury often coexist in the same model.…”
Section: Protection Against Reversible Versus Irreversible Injuries Mmentioning
confidence: 99%
“…This has been supported by reports from other groups (95,196). Recent reports also revealed that adenosine is an endogenous bioactive substance with multiple cardiovascular effects, including a negative inotropic effect, a negative contractile effect, and promotion of coronary blood flow and anti-platelet activity (90), as well as inhibition of apoptosis (158) and enhancement of autophagy (233). However, the role of elevated intramyocardial cAMP levels and PKA activation in cardioprotection of ischemic preconditioning has been reported (110), but they were both shown to be independent of PKC (117,170,176).…”
Section: Factors Underlying the Mechanisms Of Preconditioningsupporting
confidence: 56%
“…This role is mediated by microglia cells (22). But so far, no evidence has been reported that A1 adenosine receptors induce P53 expression and apoptosis, conversely, it has been shown that these receptors decrease apoptotic cell death in some cells (23,24). Our fi ndings oppose K. Sai et al results from astrosytoma RCR-1 cell line which show that A1 adenosine receptor agonist (CHA) induces apoptosis by activating caspase-9 and the ensuing caspase-3 via being linked to A1 adenosine receptor in RCR-1 cells (25).…”
Section: Discussionmentioning
confidence: 99%